Diffusion and adoption of advanced emission abatement technology induced by permit trading - Alfred Endres; Tim Friehe; Bianca Rundshagen (Journal of Public Economic Theory, 2020)
This paper analyzes firm incentives to diffuse and adopt advanced abatement technology for three different regimes of tradeable emission permits (auctioning, benchmarking, and grandfathering). We particularly consider technical change that decreases marginal abatement costs (MACs) only at high emission levels, whereas it increases them at low firm emissions. We establish that the desirability of the different regimes of allocating permits to firms is critically influenced by how MACs are changed by technological improvements.
Keywords: 330